2013
DOI: 10.1557/opl.2013.558
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Corrosion of Al Thin Films using Liquid Cell Transmission Electron Microscopy

Abstract: A fundamental understanding of the processes that occur during early stages of corrosion is traditionally limited by the dearth of techniques that probe the liquid-solid interface with both high spatial resolution and microstructural detail such as grain size and orientation. Here, we demonstrate that with a microfluidic liquid flow cell holder, we can track the progress of corrosion in situ in Al thin films with transmission electron microscopy (TEM). To mitigate the loss of resolution caused by imaging throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Figure 3 shows a series of micrographs taken from Al films exposed to 0.01 M NaCl for a total of about 15 h. Numerous, randomly dispersed blisters, a few hundred nanometers in size, were found over the entire surface of the film. These features are considerably larger and different in contrast from the pits that were observed in Al films from our earlier study (Chee et al, 2013). We believe these features to be blisters because they show up clearly in lighter contrast even when the cell is filled with liquid (Fig.…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…Figure 3 shows a series of micrographs taken from Al films exposed to 0.01 M NaCl for a total of about 15 h. Numerous, randomly dispersed blisters, a few hundred nanometers in size, were found over the entire surface of the film. These features are considerably larger and different in contrast from the pits that were observed in Al films from our earlier study (Chee et al, 2013). We believe these features to be blisters because they show up clearly in lighter contrast even when the cell is filled with liquid (Fig.…”
Section: Resultscontrasting
confidence: 91%
“…It should be noted here that corrosion experiments are very sensitive to the purity of the water used. Our earlier experiments (Chee et al, 2013) showed that Al thin films will corrode in single distilled water. For the experiments reported here, we purchased Milli-Q (Millipore Corporation) water from a commercial vendor and opened bottles were refrigerated immediately after dispensing.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…There have been many similar reports on various metals, , oxides, and alloys , in recent years. Dynamic imaging observation of corroded nanoscale microstructure features in liquid-cell TEM has exciting application prospects.…”
Section: Applications Of In Situ Liquid-cell Technology In Temmentioning
confidence: 97%
“…Thus for practical applications, one needs, on the one hand, a relatively thick liquid layer (the controlled flow and a good supply of chemical species to prevent depletion) and, on the other hand, an extremely thin layer to allow high-resolution TEM. Removing the electrolyte (e.g., water) from the NR either by evacuating the liquid using a vacuum pump or using the segmented flow of water/water–ethanol in the liquid stream would be options to increase the resolution in in situ corrosion studies in TEM (Chee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%